Analisis Persepsi Harga Terhadap Minat Beli Laptop Asus Di Kalangan Mahasiswa - Elsa Savitri; Siti Lutfiyani; Syamsul Hidayat (Institut Nalanda, 2024)
This research aims to determine price perceptions of interest in buying Asus laptops among students. This research method uses qualitative methods. The population in this study was 107 students. The sampling technique used non-probability sampling techniques with calculations using the Slovin formula to obtain a sample of 52 respondents from a total of 107 research populations. The results of the research show that price perception influences interest in buying Asus laptops among students by 42.8%. This because more students use Acer laptops because Acer laptops have lower prices with specifications that are almost similar to Asus laptops.